The Approximation of Laplace-Stieltjes Transforms Concerning Sun's Type Function. (18th June 2021) - Shen, Xia; Xu, Hong Yan
Abstract : The main aim of this paper is to establish some theorems concerning the error E n F, β, the Sun's type function U r, and M u σ, F of entire functions defined by Laplace-Stieltjes transforms with infinite order converge in the whole complex plane. Our results exhibit the growth of Laplace-Stieltjes transforms from the point of view of approximation.